2002
DOI: 10.1093/ps/81.11.1703
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early posthatch nutrition on satellite cell mitotic activity

Abstract: Myofiber growth is dependent upon the contribution of new nuclei from the mitotically active satellite cell population. The objective of this study was to examine satellite cell mitotic activity in conjunction with different nutritional paradigms during the early posthatch period. Turkey poults were provided a standard turkey starter diet; the starter diet top-dressed with a hydrated low-fat, highly digestible protein and carbohydrate nutritional hatchling supplement, Oasis; the starter diet top-dressed with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 23 publications
1
41
0
4
Order By: Relevance
“…In poultry, SCMA is an important aspect of muscle development, and the higher SCMA in newly hatched birds will result in an increase in muscle size at maturity (Mozdziak et al, 1997;Moore et al, 2005). It has been reported that early hatched nutrition increased myogenic SCMA during immediate posthatch period, and subsequently promoted BW and pectoral muscle weight during the growth phase (Mozdziak et al, 2002;Moore et al, 2005). Newly hatched broiler chicks reared Figure 2 Chick embryo (yolk-free body mass) or body weight (a), and pectoral muscle weight percentage of body weight (BW) (b) of chick embryos (E15, E17 and E19 days of age) and newly hatched male chicks (H1, H3, H5 and H7 days of age) incubated under green light or dark condition.…”
Section: Discussionmentioning
confidence: 99%
“…In poultry, SCMA is an important aspect of muscle development, and the higher SCMA in newly hatched birds will result in an increase in muscle size at maturity (Mozdziak et al, 1997;Moore et al, 2005). It has been reported that early hatched nutrition increased myogenic SCMA during immediate posthatch period, and subsequently promoted BW and pectoral muscle weight during the growth phase (Mozdziak et al, 2002;Moore et al, 2005). Newly hatched broiler chicks reared Figure 2 Chick embryo (yolk-free body mass) or body weight (a), and pectoral muscle weight percentage of body weight (BW) (b) of chick embryos (E15, E17 and E19 days of age) and newly hatched male chicks (H1, H3, H5 and H7 days of age) incubated under green light or dark condition.…”
Section: Discussionmentioning
confidence: 99%
“…It means hatchlings withheld feed and water for up to 72 h depending on the time from hatching within the hatching window to placement on rearing farms. This period is associated with a reduced in initial body weight with respect to development of gastrointestinal tract (GIT), some organs and muscles, and thus, meat yield at market age (Mozdziak et al, 2002;Halevy et al, 2003;Bhuiyan et al, 2011). Therefore, the last period of incubation has become one of the critical periods for growth, developmental programming of digestive and metabolic organs and skeleton muscles and led to the development of in ovo feeding systems for poultry (Uni et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, o TGI encontra-se imaturo durante a fase embrionária e, após a eclosão, passa a ter grande representatividade no crescimento das aves. Nos primeiros dias de vida, os segmentos do TGI sofrem sensíveis alterações morfológicas e fisiológicas que preparam a ave para o consumo e a utilização de alimentos (Mozdziak et al, 2002;Iji et al, 2001a;Noy et al, 2001;Murakami et al, 1992). Essa imaturidade do TGI de aves na fase pré-inicial reduz a capacidade de utilização dos nutrientes, o que parece acarretar decréscimo dos valores de energia metabolizável (EM) do alimento.…”
Section: Introductionunclassified